Fe-Catalyzed Bisphosphorylation of Amino-2-en-1-ones with Trialkyl Phosphites - Guo, Shengmei; Jie, Kun; Huang, Ling; Zhang, Zhebin; Wang, Yufeng; Fu, Zhengjiang; Cai, Hu (Synlett, 2019)
A facile bisphosphorylation of amino-2-en-1-ones with trialkyl phosphites mediated by iron is developed. The reaction is considered to go through two Michael addition progresses. A variety of amino-2-en-1-ones are bisphosphorylated in high yields with functional group tolerance. In addition, the protocol of introduction of two different phosphates into one molecule is successful through a cascade reaction.
Keywords: iron; bisphosphorylation; amino-2-en-1-ones; cascade reaction.